(untitled) - LESTARI, APRILIA (Language Horizon: Journal of Language Studies, 2014)
MARIA’S SELF-TRANSCENDENCE IN PAULO COELHO’S ELEVEN MINUTES Aprilia Lestari English Literature, Language and Arts Faculty, State University of Surabaya aprilialestari2604@gmail.com Diana Budi Darma, SS, M.Pd. English Literature, Language and Arts Faculty, State University of Surabaya Dianabd9@gmail.com Abstrak Studi ini mengacu pada pengalaman transendensi diri terhadap karakter utama, Maria pada novel Paulo Coelho dengan judul Eleven Minutes. Transendensi diri merupakan salah satu isu psikologi yang menjelaskan tentang kondisi diri untuk melampaui batas sebelumnya. Ada dua hal kondisi yang mungkin dapat terjadi pada transendensi diri; kondisi menjadi seorang perusak atau pencipta. Transendensi diri merupakan wujud dari pengalaman-pengalaman yang dapat menigkatkan kehidupan yang lebih baik. Tujuan dari studi tentang transendensi diri ini bertujuan untuk: (1) Membuktikan adanya transendensi diri Maria dalam novel Paulo Coelho dengan judul Eleven Minutes, (2) Serta, mengelompokkan faktor-faktor relasional yang mempengaruhi kebutuhan Maria untuk melakukan Transendensi diri dalam novel Paulo Coelho dengan judul Eleven Minutes. Pengembangan studi ini menggunakan beberapa konsep dan teori untuk dijadikan diskusi. Ada Konsep Psikologi Transpersonal milik Abraham Maslow dan dikuatkan oleh Konsep Kebutuhan Eksistensial Manusia milik Erich Fromm. Selain itu, Teori Transendensi Diri milik Pamela G. Reed juga dicantumkan sebagai bahan diskusi pengelompokan faktor-faktor relasional dari transendensi Maria. Penelitian ini menggunakan metode data yang menampilkan transendensi diri Maria sebagai perusak (melalui ketidakpercayaannya terhadap cinta; pengalaman-pengalaman seksualnya; dan keputusannya sebagai pekerja seks), dan sebagai pencipta (melalui pengalaman-pengalamnnya jatuh cinta; semangatnya untuk terus optimis; dan pengalamannya melakukan sacred-sex –hubungan seksual dengan konteks cinta). Analisis dalam studi ini dapat membuktikan bahwa transendensi diri Maria dapat meningkatkan kehidupannya menjadi lebih baik. Hal ini dipengaruhi oleh beberapa faktor-faktor relasional diantaranya: interpersonal (menghubungkan antara Maria dan keluarga, teman, dan percintaannya); intrapersonal (menghubungkan antara Maria dan pikirannya melalui tulisan-tulisan); transpersonal (menghubungkan antara Maria dan hubungan spiritualnya dengan Tuhan). Di dalam studi ini dapat disimpulkan hasil sebagai berikut: (1) Maria mengalami transendensi diri sebagai perusak dan pencipta, (2) Maria mengalami transendensi diri untuk meningkatkan kehidupannya menjadi lebih baik, melalui beberapa faktor-faktor realsional. Kata Kunci: transendensi diri, interpersonal, intrapersonal, transpersonal. Abstract This study is aimed to present self-transcendence experienced by Maria in Paulo Coelho’s Eleven Minutes. Self-transcendence is one of psychological issues described as a ‘self’ condition to go beyond previous limit. There are two possibity conditions which will be experienced in self-transcendence; condition becomes a destructor or creator. Self-transcendence embodies experiences used to improve well-being. The purposes of the study are: (1) Revealing Maria’s self-transcendence in Coelho’s Eleven Minutes, (2) Assessing the relational factors that may influence Maria’s need to experience self-transcendence in Coelho’s Eleven Minutes. To explore this study, there will be some concept and theories to discuss. They are Maslow’s Concept of Transpersonal Psychology and will be strenghtened with Fromm’s Existential Needs of Man. Additionally, Reed’s Theory of Self-Transcendence is included to assess some relational factors of Maria’s self-transcendence. This research uses data method presenting Maria’s self-transcendence as a destructor (through her mistrust about love, her sexual experiences, and her decision of being a prostitute), and a creator (through her experiences of falling in love, her spirit of optimism, and her experience of doing sacred-sex). The analysis revealed that Maria’s self-transcendence leads to improve her well-being through some relational factors, they are intrapersonal (relates Maria to her family, friend aand romance); intrapersonal (relates Maria to her mind –she used to explore her feeling through journals); transpersonal (relates Maria to her spritual connection with God). This study emerged result that (1) Maria experiences self-transcendence as destructor and creator, (2) Maria experiences self-transcendence in order to improve her well-being. To improve it, she is influenced by some relational factors. Keywords: self-transcendence, interpersonal, intrapersonal, transpersonal BACKGROUND OF THE STUDY Study of Psychology clarified that human beings belonged to animal kingdom. They have been thrown to the earth, have some functions of animal instinct. As an animal, they have some needs to be fulfilled. One of human’s needs is psychological need –including eat, drink, sleep, and sex– which becomes primary need. Furthermore, as an animal, their existence depends on nature. They are insisted to survive, they thus naturally socialize with others. In social life, human beings may have some problems to solve. To face them, human beings need to push themselves to pass their limit in order to improve well-being. One of existential needs of man which is needed to improve well-being is transcendence. It is a human being condition to insist their will for going beyond previous limit in order to achieve wellness and diminishing some negative outcomes. According to Fromm (1955), to exist, man needs to transcend the role of creator. Man can create life by planting seeds, producing material objects, creating arts and ideas, et cetera. In the act of creation, man transcends himself as a creature. On the contrary, if man can not create life so he will destroy it. To destroy life, it makes him to transcend too. Indeed, the destructiveness is being the second potentially which rooted in the existence of man. It has the same capacity and another alternative of creativeness. Maslow (1971) has similar argument with Fromm. He argued that transcendence refers to the very highest and most inclusive or holictic levels of human consciousness, behaving and relating, as ends rather than means to oneself, to significant others, to human being in general, to other species, to nature and the cosmos. Maslow emphasized that transcendence is necessary for human existence. It is able to organize mind in order to influence human’s behavior or pesonal character (self). Then, the term self-transcendence has been widely used to refer both to a process of expansion or movement beyond one’s immidiate self-boundaries (Levenson, Jennings, Aldwin, & Shiraishi, 2005). Human is the only God’s creature which is able to determine what is good or not. When they are put into difficult situations, they can survive and released themselves from boundaries. Self-transcendence thus emerges as condition of self to go beyond previous limit. In the book Middle Range Theory of Nursing: Third Edition, Reed stated that self-transcendence is expressed trough various behaviors and perspectives such as, sharing wisdom with others, integrating the physical changes of aging, accepting death as apart of life, having an interest in helping others and learning about the world, letting go of losses and finding spiritual meaning of life. Self-transcendence embodies experiences that connect rather than separate a person from self, other and environment. Person and environment are essential each other, the person’s ability experience self-transcendence thus improved well-being. Well-being is a foundational process in promoting self-transcendence. Well being may be defined in many ways, depending upon the individual or patient population. Indicators of well-being are as diverse as human perceptions of health and wellness. Examples of indicators of well-being include life satisfaction, positive self-concept, hopefulness, happiness and sense of meaning in life (M.J. Smith & P.R. Liehr, 2013). The potrayal of self-transcendence can be seen and analyzed through Paulo Coelho’s Eleven Minutes which is depicted in the main character, Maria. Eleven Minutes is a novel tells about the journeys and experiences of Maria as a young girl from Brazilian village who dreamed to get fame and fortune. At a tender age, Maria fist innocent has been bruised with love. Her first broken heart occured whe she was eleven years old. She felt in love with a boy in her journey to the way to school. She was interested with a boy but she could not express her feeling. She finally lost him She decided to fall in love again when she was fifteen years old. Unfortunately, it was not long lasting because a boy cheated with her friend. Then, Maria suddenly realized that love was the only thing to make her fall apart. She was convinced that she would never find of true love, instead of believing that “Love is a terrible thing to make you suffer.” Maria’s disappointment toward love let her start having curiosity with some sexual encounters. She experienced what no other young girls in her town had experienced before. She had some sexual experiences in kissing, making love, even self-sex like masturbation. She thus started to deem that masturbation was an alternative way to intercourse, besides she discovered that it was more fascinating. Her sexual experiences let her lose interest in serious relationship with other boys. Then, she became an adventurous and discovered many discoveries. Maria’s adventurous took her to get a chance in Rio de Janeiro in pursuit of becoming model and film career. She tripped to Switzerland to Geneva, ended it up by working as a high class prostitute. Drifting far away from love, she developed a fascination about sex such as enjoying her experiment in sadomasochism. It was one of Maria’s self-transcendences became a destructor. She was potrayed that she intentionally destructed her life. Throughout her journey as a sex-worker, she eventually found an ultimate truth about herself. After her adolescent frustation toward love, bringing Maria unto realising that her love for a painter, named Ralf Hart. In this odyssey of self-discovery, Maria’s spiritual realisation ironically sends her into a difficult decision among pursuing path of darkness, sexual-pleasure, or risking everything to find her ‘inner-light’. In this case, Maria through her self-transcendence as a creator, she experienced an eleven minutes of sacred-sex with Hart. It was a potrayal of sexual journey of prostitute yet it was Maria’s conduction as a creator. She found her true love with a man who treated her differently. RESEARCH METHOD This study is regarded as a descriptive-qualitative study. Therefore, the data will not be in number. The main source of the study is taken from a novel entitled Eleven Minutes which is written by Paulo Coelho and translated by Margaret Jull-Costa, published in 2004 by Harper Collins Publisher, New York. For collecting data, researcher does four steps to be accomplished. The first step is close-reading. Coelho’s Eleven Minutes becomes the object of the study. Besides, it aims to support in collecting and analyzing the problem of the statement. Secondly, quotating some dialogues in Coelho’s Eleven Minutes. At this point, the data are collected through noting the narration, characters’ dialogue and action in the novel, which reflects to Maria’s self-transcendence in the form of quotation. Thirdly, the data needs to calassify. For relating the study of Maria’s self-transendence, the data has to be classified into Maria’s self-transcendence (destructive and creative), which related to Fromm’s Existential Needs of Man. Afterwards, the data to be reclassified into interpersonal, intrapersonal, and transpersonal as some relational factors that may influence Maria’s self-transcendence to improve well-being, which related to Reed’s Theory of Self-Transcendence. The last step is tabling the data. To classify data into table, it is able to simplify reading data for readers. To analyze this study, there are two important steps to take. Firstly, the data has to be classified and related with the statement of problems and objectives of the study. Secondly, in analyzing the data, theories and concepts are put forward. It can be seen through Maslow’s Concept of Transpersonal Psychology as approach and will be strenghtened with Fromm’s Existential Needs of Man which transcendence becomes one of them. Furthermore, Reed’s Theory of Self-Transcendence will be discussed to reveal Maria’s self-transcendence relational factors to improve her well-being. The relational factors are interpersonal, intrapersonal and transpersonal. DISCUSSION Abraham Maslow (1971) postulated that transcendence refers to the very highest and most inclusive or holistic levels of human consciousness, behaving and relating, as ends rather than as means, to oneself, to significant others, to human beings in general, to other species, to nature, and to the cosmos. Erich Fromm has a similar argument that transcendence is one of human needs for man in order to exist. According to Fromm (1955), basically man is an animal which contents of some need to be satisfied. These needs are not rooted in his body, but those are rooted in the very peculiarity of his existence. Fromm emphasized that to solve the problem of transcending, man capable being a creator or even a destructor. In Coelho’s Eleven Minutes, the character of Maria is depicted as a young girl which has dreams to be fame and fortune. She dreams for being married by a Price Charming and living in a lovely house happily ever after, like many young girls dream too. For achieving her dreams, she experiences many things starting from being in love with some boys in her tender age and got experiencing due to heart break. In her odyssey to chase the dreams, she went to Geneva and insisted to destroy her dreams. She became a prostitute temporarily and decided to stop it after her meeting with Ralf Hart. He was the one who confessed her inner-light. Then, she finally experienced an eleven minutes of sacred-sex with him, and got multiple-orgasm. In this analysis, Maria is a subject of analysis who experienced self-transcendence as a destructor and creator. To go beyond limit, man not only capable create but also destroy life. Fromm (1955) postulated, “If I cannot create life, I can destroy it. To destroy life makes me also transcend it.” Indeed, man can destroy life is just a miraculous a feat as that he can create it, for life is the miracle, the explicable. In the act of destruction, man sets himself above life; he is driven to transcend himself, to create or to destroy, to love or to hate. Maria’s conduction of destructor is presented when she mistrust about love; through her sexual-experiences; and her decision to work in prostitution. Besides being a role of destructor, Maria also creates her life better. Fromm (1955) emphasized that Man can create life; Man–man and woman–can create life by planting seeds, by producing material objects, by creating art, by creating ideas, by loving one another. In the act of creation man transcend himself as a creature, raises himself beyond the passivity and accidentalness of his existence into the realm of purposefulness and freedom. In Coelho’s Eleven Minutes Maria is described as a girl who faces many problems since she was in adolescent. She gets downs and being into difficult situations. She thus leads to destruct herself. She destructed her dreams, her believing, and many others. But, in her spirit of optimism she wakes up becoming creator. Her conductions of creator can be shown when she experienced to fall in love; view her spirit of optimism; and her experience of sacred-sex, a sex in the content of love. Self-transcendence experiences to promote well-being. Maria is explained as a girl who destruct her life then she finally create it being better. To improve her well-being, she is influenced by some relational factors. Reed’s Theory of Self-Transcendence is discussed in this study, to reveal Maria’s self-transcendence which is influenced by some relational factors, such as interpersonal, intrapersonal, and transpersonal. Reed’s Theory of Self-transcendence is major by two assumptions. Firstly, it is assumed that human beings are integral with their environment. They coextensive with their environment and capable to extend physical and temporal dimensions. It may experiences through altered state of consciousness such as, reaching deeper within self to others, to nature, to one’s God, or many other sources of transcendence. The second assumption that self-transcendence is a developmental imperative, which means human resource that demands expression, much like other developmental processes, such as walking in toddlers, abstract reasoning in adolescents, and grieving in those who have suffered a loss (Mary, J.S. & Patricia, R.L., 2004). According to Reed, self-transcendence refers to the capacity to expand self-boundaries in a variety of ways. Some of these are as follows: intrapersonally (toward greater awareness of one’s philosophy, values, and dreams), interpersonally (to relate to others or one’s environment), temporally (to integrate one’s past and future in a way that has meaning for the present), and transpersonally (to connect with the dimensions beyond the typically discernible world). It is obvious that Reed’s Theory of self-transcendence was presented to heal and reaching well-being. To assess Maria’s self-transcendence, there are some relational factors that may influence her to experience self-transcendence to reach well-being. Firstly, the interpersonal factor which relates between her and family–especially for her mom; friends; and romance–especially for Ralf Hart. Secondly, the intrapersonal factor which relates her with her personal self or mind. She used to write a diary about her life. Her habitual of writing journals be able to influence her to reach well-being. Thirdly, is a transpersonal factor which relates between her and something more powerful or greater than herself, that is God. This spiritual connection enables men to use their temporal perspectives to empower themselves. They will synchronize their life with realities, becoming a ventilator, then being able to manage their life more healthy (Mary, J.S. & Patricia, R.L., 2004). CONCLUSION Paulo Coelho is appropriate in awarding many prizes. His novel Eleven Minutes contains many factual issues related to the psychological aspect. Self-transcendence is one of psychological aspects that every human needs to experience. It is described as a self condition for going beyond previous limit. It is the highest human consciousness because it is able to influence mind to reach well-being. This study takes an issue according to the main character, Maria. She experiences self-transcendence as a destructor and creator. She experiences it to reach well-being. To achieve well-being, she is influence by some relational factors, such as interpersonal, intrapersonal, and transpersonal. Based on the analysis, it can be inferred into two conclusions; the first conclusion to answer the first statement problem that Maria’s self-transcendence is revealed through her conductions of becoming destructor and creator. The conduction of destructor is shown through her mistrusting toward love, since she was in school. Then, another conduction of destructor is shown when Maria experimented sexual experiences with many boys. She is interested to find new discovery about sex. She is always curious how pleasure to have sex with partners, that is why she experiences many sexual-experiments. The last conduction of destructor is shown when she intentionally decides to become a prostitute. In her odyssey to chase her dreams, she is sent to Geneva, Swiss. She is alone there. She needs more money to survive, that is why she decides to join prostitution. Because it guarantees her life for a couple months later. Maria’s self-transcendence is not only shown as a destructor. She also become a creator because she wants to reach well-being. Maria’s conduction of becoming creator is shown when she is fallen in love with many boys. Although her adolescent process is dominated with love trauma, she is always optimist. She experiences many things in her way to chase her dreams. Despite she gets ups and downs, she always has spirit of optimism to survive. Another Maria’s conduction which leads her to become creator, when she experiences eleven minutes of sacred-sex (sex, in the content of love) with Ralf Hart. Ralf Hart is a painter who said that Maria has a special inner-light. It was a potrayal of sexual journey of prostitute yet it was Maria’s conduction becomes a creator. She found her true love with a man who treated her differently. The second conclusion is to answer the second statement problem. Maria experiences self-transcendence in order to improve her well-being. To improve it, she is influenced by some relational factors. According to Reed, some relational factors that may influence Maria are interpersonal (between her and her family, friend, and romance), intrapersonal (between her and her mind, which is explored in her journals), and transpersonal (between her and her spiritual connection with God). GRATITUTION Alhamdulillah, I praise to Allah SWT for His kidness, I finally finished this journal. My great gratitude to Mrs. Diana Budi Darma, SS, M.Pd as my advisor for her attention and advice. I also thanked to my parents who always love, care, give advices, and strengten me to complete my study and finishing my journal. REFERENCES Bachofen, J.J. 1967. Myth, Religion, and Mother Right: Selected Writings of Johan Jacob Bachofen (R. Manheim, Trans.). Princeton, NJ: Princeton University Press. Coelho, Paulo. 2004. Eleven Minute (Translated From Portuguese by Margaret Jull Costa. New York: Harper Collins. Ferrer, J.N., 2002. Revisioning Transpersonal Theory: A Participatory Vision of Human Spirituality. New York: State Universiy of New York Press. Fromm, Erich. 1955. The Sane Society. New York: Holt, Rinehart & Winston. Maslow, A. H. 1964. Religions, Values, and Peak-Experiences. USA: Kappa Delta Pi. Maslow, A. H. 1970. Motivation and Personality: Second Edition. New York: Harper & Row. Mary, J. S., Patricia, R. L. 2004. Middle Range Theory: Third Edition. New York: Springer Publishing Company, LLC. Reed, P. G. 1996. Transcendence: Formulating Nursing Perspectives. Nursing Science Quaterly, Journal, 2-4. Rogers, M. E. 1980. A science of Unitary Man: Second Edition. New York: Appleton-Century-Cloft. Semiun, Y. 2013. Teori-Teori Kepribadian Psikoanalitik Kontemporer: Jilid 2. Yogyakarta: Penerbit Kanisius . INTERNET SOURCES http://www.harpercollins.com/author/microsite/about.asx?authorid=1858 retrieved at Tuesday, October 15th 2013. http://www.santjordiasociados.com/ozahir/eng/print/biography_coelho.pdf retrieved at Tuesday, October 15th 2013. http://wiki.answers.com/Q/What_are_Paulo_Coelho’s_awards retrieved at Tuesday, October 15th 2013. http://www.stanislavgrof.com/pdf/A%20Brief%20History%20of%20Transpersonal%20Psychology-Grof.pdf retrieved at Friday, September 20th 2013. http://www.sofia.edu/content/transpersonal-pioneers-abraham-maslow retrieved at Monday, September 23rd 2013. http://www.rivier.edu/faculty/pcunningham/Research/Chapter_1_Introduction_to_Transpersonal_Psychology.pdf retrieved at Tuesday, September 10th 2013.